Structural Biology Illuminates Molecular Determinants of Broad Ebolavirus Neutralization by Human Antibodies for Pan-Ebolavirus Therapeutic Development - Murin, Charles D.; Gilchuk, Pavlo; Crowe, James E.; Ward, Andrew B. (Frontiers in Immunology, 2022)
Monoclonal antibodies (mAbs) have proven effective for the treatment of ebolavirus infection in humans, with two mAb-based drugs InmazebTM and EbangaTM receiving FDA approval in 2020. While these drugs represent a major advance in the field of filoviral therapeutics, they are composed of antibodies with single-species specificity for Zaire ebolavirus. The Ebolavirus genus includes six additional viruses, two of which, Bundibugyo virus and Sudan virus, have caused severe disease and significant outbreaks in the past. There are several recently identified broadly neutralizing ebolavirus antibodies, including some in the clinical development pipeline, that have demonstrated broad protection in preclinical studies. In this review, we describe how structural biology has illuminated the molecular basis of broad ebolavirus neutralization, including details of common antigenic sites of vulnerability on the glycoprotein surface. We begin with a discussion outlining the history of monoclonal antibody therapeutics for ebolaviruses, with an emphasis on how structural biology has contributed to these efforts. Next, we highlight key structural studies that have advanced our understanding of ebolavirus glycoprotein structures and mechanisms of antibody-mediated neutralization. Finally, we offer examples of how structural biology has contributed to advances in anti-viral medicines and discuss what opportunities the future holds, including rationally designed next-generation therapeutics with increased potency, breadth, and specificity against ebolaviruses.